Lexikalische Kompetenz – ein Plädoyer für eine breitere Auffassung des Begriffs - Targońska, Joanna (Glottodidactica, 2011)
The subject of the present paper is the notion of ‘lexical competence’. This type of competence is often analysed in a too narrow sense, although over the years the notion has been broadened. Since in the Author’s opinion the definition of lexical competence should include not only the knowledge about vocabulary or its usage, but also the ability to compensate for lexical gaps, a new, slightly broader definition has been formulated and the factors were presented which may influence its development